The Role of Aerosols in Convective Processes during the Midsummer Drought in the Caribbean - Nathan Hosannah; Hamed Parsiani; Jorge E. González (Advances in Meteorology)
Saharan dust (SD) heavily impacts convective precipitation in the Caribbean. To better understand the role of SD in precipitation development during the midsummer drought (MSD), an observational campaign, centered at the city of Mayagüez, Puerto Rico (18.21 N, 67.13 W), between 3 June and 15 July 2014, was conducted in order to select a range of atmospheric conditions to be simulated using the Regional Atmospheric Modeling System (RAMS) cloud resolving model under “no SD” and “SD” conditions. The events included one dry day with moderate-heavy SD, one localized moderate rainfall event with moderate SD, one island-wide light precipitation event with heavy SD, and one island-wide heavy precipitation event with light-moderate SD. Model results show that (1) precipitation results are improved when compared with observation with the presence of SD, (2) precipitation, cloud fraction, dew point temperatures, and humidity are significantly reduced under SD conditions, (3) precipitation can occur when SD is removed for a dry day, (4) there is evidence of rain being delayed due to the presence of SD without rainfall intensity or accumulation increases, (5) liquid mixing ratio increases of up to 1.4 g kg−1 occur in the absence of SD, and (6) vertical wind increases of up to 0.8 m s−1 occur in the absence of SD.